Enhancing Financial Performance Assessment: A Fundamental Analysis of PT. Bank Syariah Indonesia, Tbk. in The Capital Market (2019-2023) - Niu, Fitria Ayu Lestari; Jan, Radlyah Hasan; Tubagus, Sofyan Oktavian (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2023)
This study aims to provide an overview of the financial performance of PT. Bank Syariah Indonesia, Tbk. uses real data in the capital market based on fundamental analysis using descriptive quantitative research. This study uses secondary data, namely the financial statements with samples of 2019 before the merger until 2023 Quarter 3. This data was analyzed using fundamental analysis. The results found that PT. Bank Syariah Indonesia, Tbk. in these 2 years there has been an increase in free float by 4.92%, but this does not affect its share price, which experiences fluctuations, moving downward in 2022 to 2023, around the lowest price of IDR 1,200,-. Besides it, the fundamental matrix assessment shows the amount of revenue obtained by PT. Bank Syariah Indonesia, Tbk from the P/E ratio of 14.61 and the P/S ratio of 3.15. Meanwhile, the value (P/E) in 2022 has decreased dramatically to 11. Growth and profitability moved positively from 2018 to 2022 amounting to 22 trillion. Net margin, which had fallen in 2019, rose dramatically, especially in 2022, to 20% and routinely fulfilled its obligations to investors by distributing dividends in 2021 of 17,952 and 9,235 in 2022. PT. Bank Syariah Indonesia, Tbk. provides quite a lot of financing to customers with a ratio of 3: 1 compared to customer deposits. This needs to be considered, careful and pay attention to providing financing, especially in consumption financing which will result in bad loans or liquidity problems